2020
DOI: 10.1080/10503307.2020.1823030
|View full text |Cite
|
Sign up to set email alerts
|

Does it make a difference to be more “on the same page”? Investigating the role of alliance convergence for outcomes in two different samples

Abstract: To better understand the complexity of dyadic processes, such as the mechanisms of the working alliance, researchers recommend taking advantage of innovations in data analytic procedures when studying the interactions between therapists and patients that are associated with favorable therapeutic outcomes. Inspired by a recent line of alliance research using dyadic multilevel modeling, the present study investigated the hypothesis that convergence in the patient-therapist working alliance (i.e., increased simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…The relationship between client and therapist – or service user and Music Therapist – can be understood as essential to the therapeutic outcome in and of itself (Nissen-Lie et al, 2021; Wampold and Imel, 2015). As Wampold and Imel (2015) point out, a human connection with an empathetic and caring individual ought to be health-promoting, particularly for individuals who can experience challenges with social relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between client and therapist – or service user and Music Therapist – can be understood as essential to the therapeutic outcome in and of itself (Nissen-Lie et al, 2021; Wampold and Imel, 2015). As Wampold and Imel (2015) point out, a human connection with an empathetic and caring individual ought to be health-promoting, particularly for individuals who can experience challenges with social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for people who have challenges in social functioning, a human connection with an individual (i.e. the therapist) who is empathetic and caring is likely to be health-promoting (Nissen-Lie et al, 2021; Wampold and Imel, 2015). This resonates with Rogers’ 1957 theory, which posits that the critical processes in the client–therapist relationship depend on empathy.…”
Section: The Therapeutic Relationshipmentioning
confidence: 99%
“…It should be noted that therapists' and clients' perceptions are not always discrepant. In fact, some recent studies have found that the degree to which therapists and clients converged in their identification of important change moments correlated with outcome (Nissen-Lie et al, 2020). In one study, clients and therapists did agree on the basic nature of the change process even if they did not identify the same change moments (Altimir et al, 2010).…”
Section: Client Contributions To the Meeting Of Mindsmentioning
confidence: 97%
“…This limitation reflects the main trend in therapeutic alliance studies that mostly focus on patients' views only (30). However, recent studies have highlighted the importance of taking into account both patient and therapist perspectives, introducing the concept of patient-therapist alliance "congruence" (i.e., the inter-rater agreement on alliance quality at one time-point) and the alliance "convergence" (i.e., the degree of change over time in the inter-rater agreement on alliance quality) (99)(100)(101). These constructs reflect the dynamic nature of this dyadic process and carry complementary information on a therapeutic relationship that is asymmetric by nature (102).…”
Section: Alliance Measurementmentioning
confidence: 99%